2000
DOI: 10.1108/00368790010317366
|View full text |Cite
|
Sign up to set email alerts
|

Grease‐lubrication of roller bearings in railway waggons. Part 2: laboratory tests and selection of proper test methods

Abstract: New, undestroyed greases of the same brands as those used in a field test, described in Part 1, were examined using conventional methods, such as the SKF V2F test, the roll stability test (ASTM D‐1831), the Grease Worker (ASTM D‐217), the torque test (ASTM 1478‐91), bleeding measurements ( IP 121), yield stress measurements, the 4‐ball test (ASTM D 2266‐86), base oil viscosity measurements, thickener content and the cone penetration test (ASTM D217‐88). The greases have also been tested with several new test m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…This model has also been applied to the other three selected rheological properties: storage modulus G 0 , crossover stress t c , and yield stress t y ¡ OSC from the oscillatory test in the form of Eq. [7], called here the grease aging equation:…”
Section: Thermodynamic Characterization Of Grease Mechanical Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…This model has also been applied to the other three selected rheological properties: storage modulus G 0 , crossover stress t c , and yield stress t y ¡ OSC from the oscillatory test in the form of Eq. [7], called here the grease aging equation:…”
Section: Thermodynamic Characterization Of Grease Mechanical Degradationmentioning
confidence: 99%
“…A typical mechanical stability test is the roll stability test (ASTM D 1831), where grease is sheared between a heavy roller (with a lead core) and a hollow rotating cylinder at an elevated temperature (generally 80 C). It was found that this test can be used to simulate the practical working conditions in automobile wheel bearings (Bondi,et al (4); Moore and Cravath (5)), and rolling bearings in railway wagons (Lundberg (6); Lundberg and Berg (7)). The other test is the shear stability test, where only shear is applied.…”
Section: Introductionmentioning
confidence: 99%
“…This has serious implications on grease performance, since lubricating greases should be attached to the seals, bearing shoulders or cage, forming a lubricant reservoir and providing a sealing action. Without a proper viscoelastic behavior under low stress level (G > G ), lubricating greases cannot provide an appropriate lubrication, as observed by Lundberg et al [18,36]. Figure 6 shows the central film thickness versus the entrainment speed of the fresh lubricating greases, their corresponding base and bled oils at a constant temperature of ≈40 • C .…”
Section: Rheological Analysis Of the Lubricating Greasesmentioning
confidence: 91%
“…Grease aging was performed in two stages: (i) the grease was sheared during one hour using a roll stability tester to simulate the grease churning phase; (ii) then, a layer of 1 mm of the sheared grease was spread in a steel plate, which was kept rotating during 72 h at 130 • C in an oven with forced air convection. The roll stability tester was shown to be the best way to simulate the mechanical work in rolling bearings by Lundberg et al [18], and the thermal aging of thin layers of lubricating greases was shown to represent the aging of grease-lubricated rolling bearings well [19].…”
Section: Aging Processmentioning
confidence: 99%
“…During operation, when the grease is coming into contact with the rollers and rings of the bearing, this will lead to the mechanical degradation of the grease, as the bearing is acting like a mill [1] . The result can thus be weakening of the consistency of the grease, which will entail higher demands on the sealing properties in order to prevent the grease from leaking out of the box and thus the bearing [2] . Since the sealing properties are dependent on viscosity of the sealed lubricant [3] , it can be assumed that, if the consistency is below a critical value, then the grease will flow out of the box, resulting in lubrication starvation and seizure of the bearings [4] .…”
Section: Introductionmentioning
confidence: 99%